Pathological changes in mucous membrane and microcirculatory bed vessels of rats oral cavity at modeling of diabetes mellitus - Rozhko, P. D.; Gargin, V. V. (Journal of Education, Health and Sport, 2020)
At experimental modeling of diabetes mellitus type II in rats, ischemic and dystrophic processes develop in periodontal tissues. It leads to emergence of destructive-inflammatory processes in animals and one of their pathogenic factors is apoptosis activation and compensatory activation of angiogenesis as evidenced by 1.81 times increase of monoclone BAX and 2.89 times increase of VEGF. The pathological processes mentioned should be taken into account in the development of therapeutic and prophylactic complexes of accompanying orthopedic treatment for diabetes mellitus patients.